Sufism Healing Methods for Drug Rehabilitation in Inabah of West Java, Indonesia - Rusmana, Asep; Wan Ali, Wan Zailan Kamaruddin (TEMALI : Jurnal Pembangunan Sosial, 2022)
Sufism activities include not only rituals but also pseudo-medical treatment. This can be seen from the daily life of the Qadiriyyah and Naqsabandiyah (TQN) congregation at the Suryalaya Islamic Boarding School, Tasikmalaya, West Java. Known as a center for Islamic learning, this pesantren also offers spiritual healing, namely inabah to cure drug victims. This study aims to explore this Sufi inabah . Based on a qualitative ethnographic study at this site, the study analyzes explicitly a method of treatment called inabah. This is a unique technique used by Sufis to cure drug patients. This study shows that the Sufis provide spiritual and technical guidance in the treatment process to increase the awareness of drug victims through quasi-medical and spiritual processes. In the view of the Sufis, drugs can be cured by growing spiritual activities, such as remembrance and prayer. More than that, this method also requires the practice of realized repentance, fasting, bathing, and other related processes prescribed by Sufi masters. The process of fulfilling spiritual and physical requirements due to illness or disease is seen as the result of spiritual and physical transgression.